Breakfast Cereals Intended for Children: Opportunities for Reformulation and Potential Impact on Nutrient Intake - Mariana Santos; Filipa Matias; Ana Isabel Rito; Isabel Castanheira; Duarte Torres; Isabel Loureiro; Ricardo Assunção (Foods, 2021)
Ready-to-eat cereals (RTECs) have become a popular breakfast option claiming to provide important nutrients to children’s diets, despite being a source of excess sugar and, therefore, a health concern. Thus, food reformulation constitutes an important public health strategy that could benefit from inputs provided by nutrient profiling. This study aimed to assess the adequacy of the RTECs for children available in Portuguese supermarkets, applying three nutrient profile models (NPMs)—the nutrient profile model of the World Health Organization’s Regional Office for Europe (WHO-EURO), the profile of the private-sector EU Pledge (EU-Pledge), and the national model developed by the Directorate-General of Health (NPM-PT)—in order to explore the potential for reformulation of the RTECs identified as not adequate and evaluate the impact of RTECs’ reformulation on the nutritional quality of Portuguese children’s diets. In total, 78 RTECs intended for children were assessed and two scenarios—current (not considering reformulation) and alternative (considering reformulation to accomplish the nutrient profile requirements)—were considered to assess the impact of reformulation on nutritional quality. Across all RTECs, only 5.1% could be promoted to children according to the considered NPMs. The most common nutrients requiring reformulation were sugar, saturated fatty acids (SFA), salt, and dietary fiber. The scenarios of reformulation considered could reduce the RTECs average content of total sugars, SFA, and salt by 43%, 8.7%, and 1.1%, respectively, and dietary fiber intake could be increased by 34%. Thus, these results support policies to implement reformulation strategies for developing healthier food products to be promoted to children.